Peran Agunan dalam Penyelesaian Pembiayaan Produktif Bermasalah pada Bank Syariah - Wardi, Lalu Suryamukty Primaditya; Muslihun, Muslihun; Sanurdi, Sanurdi (Jurnal Ilmu Sosial dan Humaniora, 2024)
Non-performing financing (NPF) is very common in Sharia banking, which is the main reason the availability of collateral from the customer is considered very important. This research aims to examine the role of collateral in resolving problematic productive financing, especially at PT Bank NTB Syariah Praya. The method used in this research is descriptive qualitative where researchers collect data through observation, documentation, and in-depth interviews with customers and employees of PT Bank NTB Syariah Praya. The data was then analyzed by reducing them into more concise and relevant data, presented in the form of interview quotations that were easy to understand, and relevant conclusions were drawn based on the interpretation of the data collected. The results of this research indicate that PT Bank NTB Syariah Praya requires its customers to provide collateral when applying for financing and is committed to auctioning collateral if the customer is unable to complete the financing received for any reason and if the bank believes that the customer will not be able to complete the financing in the future. However, this is hampered by a mismatch in the type of collateral provided by customers. The results of this research can be a basis for banks to review policies regarding the types of collateral allowed as a form of mitigating the risk of the emergence of more NPFs.